2017
DOI: 10.1177/2325957417732834
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Condom Use with Paying and Nonpaying Partners among Female Sex Workers in Iran: Findings of a National Biobehavioral Survey

Abstract: Our findings indicated the urgent need for scaling up condom promotion interventions catered toward FSWs and their sex partners to practice safe sex consistently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Compared with STI prevalence among the general female population in Iran,26 27 FSWs have a higher STIs prevalence due to unsafe sex with multiple partners. We found almost no improvement in safe sex practices among FSWs from the 2010 to the 2015 surveys 3 9. Several individual and structural barriers to consistent use of condoms among FSWs in Iran have been reported 3 28.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Compared with STI prevalence among the general female population in Iran,26 27 FSWs have a higher STIs prevalence due to unsafe sex with multiple partners. We found almost no improvement in safe sex practices among FSWs from the 2010 to the 2015 surveys 3 9. Several individual and structural barriers to consistent use of condoms among FSWs in Iran have been reported 3 28.…”
Section: Discussionmentioning
confidence: 64%
“…We found almost no improvement in safe sex practices among FSWs from the 2010 to the 2015 surveys 3 9. Several individual and structural barriers to consistent use of condoms among FSWs in Iran have been reported 3 28. Innovative interventions that address these barriers and reach underserved FSWs are needed.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Consistent condom use during paid sex is essential for reducing sexually transmitted infections (STIs), including HIV/AIDS [1,2]. HIV/AIDS has been one of the greatest contributors to the global mortality rate [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, research on condom use among men has mainly been conducted in Asian countries such as Cambodia [ 19 ], China [ 20 , 21 ], India [ 22 – 24 ], Singapore [ 25 ], Indonesia [ 26 ], with a few focusing on Middle East [ 1 ] and Africa [ 27 , 28 ]. Generally, such studies have revealed the predictors of consistent condom use among homosexual males [ 19 , 27 , 29 ], young dating adults [ 30 ], and men who patronize paid sex [ 22 ].…”
Section: Introductionmentioning
confidence: 99%